Gene Expression of MicroRNA-370 in Some Iraqi Women with Breast Cancer - Mahood, Wafaa Sabri; Hasan, Maryam Jasim; Mohammed, Mohammed Jasim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Breast cancer becomes a major threat to female health, many reports refer to a high incidence of breast cancer in Iraq; especially, in the last years. The micro RNA-370 molecules have not been reported in Iraqi cancer patients. Our objective in this study was to identify the expression of micro RNA-370 molecules in breast cancer patients as an early detection biomarker of breast tumors and detect its relation with clinicopathological characters of breast cancer patients. Fifty fresh tissue samples were collected from benign and malignant breast patients in addition to ten normal tissue samples collected as a control group, the age ranged was(19 - 77) years for patients. The miR-370 gene expression level was measured by the quantitative real-time reaction (qRT-PCR). Our results demonstrate a high expression ofmiR370 in benign and malignant tissues. The miR‑370 expression level was inversely correlated with the age of the patients. It was a significant relation of miR‑370 gene expression on the left side of breast malignant (p- 0.05). In conclusion, significantly associated with high miR-370 expression were found depending on age, tumor location, tumor type, and stage of differentiation. The upregulation of miR-370 gene expression in benign lesions and breast cancer tissue can be applied as a biomarker for early breast cancer detection